Analisis Literatur Sistematis Model Jigsaw sebagai Strategi Peningkatan Hasil Belajar Bahasa Indonesia di Jenjang Sekolah Dasar - Halfi Desyolina; Izatul Hafifa; Maulia Nur Rezki; Dinda Wahyuni; Apfani Apfani (Universitas Serambi Mekkah, 2025)
This study aims to examine the effectiveness of the Jigsaw learning model in improving Indonesian language learning outcomes for elementary school students through a systematic literature analysis approach. The primary focus of this study is to identify the contribution of the Jigsaw model to students' academic achievement, learning engagement, social skills, and critical thinking skills in Indonesian language learning. The method used was a systematic literature review of various scientific articles and research findings. The collected data was then analyzed thematically. The study results indicate that the application of the Jigsaw model consistently has a positive impact on improving Indonesian language learning outcomes. Students learning with the Jigsaw approach demonstrated better understanding, higher engagement in the learning process, and improved communication and collaboration skills. However, challenges in group management and learning time are important considerations that teachers need to anticipate. These findings strengthen the relevance of the Jigsaw model as an effective learning strategy at the elementary school level.